Interest Group Access to the Bureaucracy, Parliament, and the Media - Binderkrantz, Anne Skorkjær; Christiansen, Peter Munk; Pedersen, Helene Helboe (Governance (Oxford), 2015)
A key issue for interest groups and policymakers is the ways through which organized interests voice their interests and influence public policy. This article combines two perspectives on interest group representation to explain patterns of interest group access to different political arenas. From a resource exchange perspective, it argues that access to different political arenas is discrete as it is determined by the match between the supply and demands of interest groups and gatekeepers—politicians, bureaucrats, and reporters. From a partly competing perspective, it is argued that access is cumulative and converges around wealthy and professionalized groups. Based on a large‐scale investigation of group presence in Danish political arenas, the analyses show a pattern of privileged pluralism. This describes a system where multiple political arenas provide opportunities for multiple interests but where unequally distributed resources produce cumulative effects (i.e., the same groups have high levels of arena access).